Effect of Female Age on Crossing Over Frequency in Drosophila melanogaster Crosses N x bcl and N x ym and Their Reciprocals - Savitri, Lisa; Kasimo, Elfred Rinaldo; Krissanjaya, Rochmad; Juwita, Syntia Tanu; Antoro, Ester Lianawati; Wulansari, Ida Septika (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Crossing over is the occurrence of disconnection and reconnection followed by a reciprocal exchange between the two chromatids in a bivalent form. The crossing event will produce parental type and recombinant type. In the event of crossing over, various factors can influence it. These factors can be due to internal and external. Recently, various factors have been reported that influence the incidence of crossing over. These factors include age, temperature, radiation, and changes in chromosome structure. This research is a type of experimental research that uses a randomized block design. Randomized block design by crossing D. melanogaster strains ?N>< ?bcl and ?N>< ?ym and their reciprocals. From the results of this cross (F1) then cross again ?N with the recessive male (from stock) then observe the phenotype of the offspring (F2) and calculate the results of the offspring. The F2 ?N crosses were treated with age variations, namely 0, 3, 6, 9, 12, 15, and 18 days. Based on the results of these crosses, the derived strains that appeared in the F2 crosses showed the phenomenon of crossing over with the influence of the age of the female and the type of strain on crossing events. the frequency or value of crossing over (formation of recombinants) decreased with the increasing age of the female. If the age of the female affects the frequency of crossing over, then the older the female, the more likely the frequency of crossing over will decrease. However, because the data obtained were incomplete, it was not possible to know the effect of female age on the frequency of crossing over of D. melanogaster crosses ?N>< ? bcl and ?N >< ?ym and their reciprocals. The condition for crossing over is the formation of a synaptonemal complex. Age of D. melanogaster females has an effect on the frequency of crossing over in crosses N? >< bcl?, N? >< ym?, and their reciprocals. The older Drosophila melanogaster is, the lower the frequency of crossing over will occur. Based on this, it was necessary to cross D. melanogaster with strains N, bcl, and ym. A cross consists of ?N ><?bcl and ?N ><?ym and their reciprocals. By crossing ?N with a recessive male from the stock, then observing the F2 phenotype, it is hoped that crossing over will occur. So that you can better understand by doing the practice directly. In this case, the effect of crossing over is seen from the age of the female and the type of strain.